Dual-Enhanced Pluronic Nanoformulated Methotrexate-Based Treatment Approach for Breast Cancer: Development and Evaluation of In Vitro and In Vivo Efficiency - Amira Mansour; Mohamed Y. Mahmoud; Alaa F. Bakr; Monira G. Ghoniem; Fatima A. Adam; Ibrahim M. El-Sherbiny (MDPI AG, 2022)
Breast cancer is a prevalent tumor and causes deadly metastatic complications. Myriad cancer types, including breast cancer, are effectively treated by methotrexate (MTX). However, MTX hydrophobicity, adverse effects and the development of resistance have inspired a search for new effective strategies to overcome these challenges. These may include the addition of a bioenhancer and/or encapsulation into appropriate nano-based carriers. In the present study, the anticancer effect of MTX was fortified through dual approaches. First, the concomitant use of piperine (PIP) as a bioenhancer with MTX, which was investigated in the MCF-7 cell line. The results depicted significantly lower IC50 values for the combination (PIP/MTX) than for MTX. Second, PIP and MTX were individually nanoformulated into F-127 pluronic nanomicelles (PIP-NMs) and F-127/P-105 mixed pluronic nanomicelles (MTX-MNMs), respectively, validated by several characterization techniques, and the re-investigated cytotoxicity of PIP-NMs and MTX-MNMs was fortified. Besides, the PIP-NMs/MTX-MNMs demonstrated further cytotoxicity enhancement. The PIP-NMs/MTX-MNMs combination was analyzed by flow cytometry to understand the cell death mechanism. Moreover, the in vivo assessment of PIP-NMs/MTX-MNMs was adopted through the Ehrlich ascites model, which revealed a significant reduction of the tumor weight. However, some results of the tumor markers showed that the addition of PIP-NMs to MTX-MNMs did not significantly enhance the antitumor effect.